Surgical management of intracranial hypertension in rickets-related craniosynostosis - Alessio Iacoangeli; Sergio Capelli; Andrea Held; Emidio Procaccini; Davide Luglietto; Matteo Barba; Alessandro De Benedictis; Carlo Gandolfo; Carlo Efisio Marras (Interdisciplinary Neurosurgery)
Hypophosphatemic rickets is occasionally associated with craniosynostosis. Delayed diagnosis can result in intracranial hypertension, potentially leading to serious neurological complications. We report the case of a 9-year-old boy with X-linked hypophosphatemic rickets who presented with headache, fundus oculi edema, and double sinus pericranii. A CT scan revealed fusion of the cranial sutures, and continuous intracranial pressure monitoring confirmed intracranial hypertension. The patient successfully underwent bilateral cranial expansion. Secondary craniosynostosis is a rare condition, with hypophosphatemic rickets being the most common metabolic cause. Sinus pericranii is a rare radiological manifestation of intracranial hypertension. Craniosynostosis presenting after infancy or early childhood should prompt consideration of secondary or metabolic causes. Regular monitoring for head shape abnormalities and signs of intracranial hypertension is essential in patients with hypophosphatemic rickets. Skull expansion is an effective therapeutic option.